Analysis Of Psychological Factors Associated With Decreased Appetite In The Elderly - Djusmadi Rasyid; Rezqiqah Aulia Rahmat (International Journal of Health Sciences, 2026)
Appetite loss ( anorexia of aging ) is a common condition among older adults and is associated with an increased risk of malnutrition , muscle loss , frailty , reduced quality of life , and higher morbidity and mortality . In addition to biological factors and chronic diseases , psychological conditions such as depression , anxiety , loneliness , psychological stress , and inadequate family support are considered important contributors to appetite declin. To analyze psychological factors associated with appetite loss among community dwelling older adults . A total of 306 older adults were selected using proportionate stratified random sampling . Appetite loss was assessed using the Simplified Nutritional Appetite Questionnaire (SNAQ) . Independent variables included depression , anxiety , loneliness , psychological stress , family support , social support , physical activity , nutritional status, chronic diseases , and sleep quality. Appetite loss was identified in 38.9% of participants, anxiety (p=0.003), loneliness (p=0.001), psychological stress (p=0.005), family support (p<0.001), physical activity (p=0.002), nutritional status (p=0.001), and sleep quality (p=0.008). Multivariate analysis revealed that depression was the strongest associated factor (OR=4.32; 95% CI=2.31–8.09), followed by poor family support (OR=3.47; 95% CI=1.88–6.40) and loneliness (OR=2.85; 95% CI=1.54–5.28). Psychological factors are significant associated with appetite loss among community dwelling older adults . Depressed , inadequate family support , and loneliness were the most influential Mental health factors screening , strengthening family support , and promoting social engagement is recommended to prevent malnutrition and improve the quality of life of older adults .